O DESENVOLVIMENTO DA CRÍTICA À IDOLATRIA DO MERCADO EM HUGO ASSMANN. - SOUZA, THADEU DA SILVA (2017)
This research seeks to investigate the theoretical methods used by the latin-american theologian Hugo Assmann to articulate the binomial theology and economics in the task of criticizing the religious functioning of capitalism. For an adequate analysis, we restrict ourselves to analyse the devolopment of his criticism to the idolatry of the market. By making use of Jung Mo Sung's contributions we have divided Assmann's thoughts in three phases very different in his understanding about the market.We seek to analyse in detail each one of the phases in the next chapters that constitute this dissertation starting from his main works. In the first chapter, we dedicated ourselves to study Assmann's criticism to the "capitalismo como religião do fetiche". Our hypothesis is that this criticism is the first register that critically links the market to the biblical concept of gods and idols. In this phase Assmann develops a radical or metaphysics critique of the capitalist market, disregarding the importance of the market in a possible postcapitalism/socialism society. The second chapter approaches the theme of the market idolatry from Hugo Assmann. After that, we analyse both of the major concepts of this structure: idol and idolatry. We showed that, by the time he made use of the thesis of Franz Hinkelammert about Crítica da razão utópica, Assmann begins to accept the market as a necessary economic factor to social relations. His criticism is toward the absolutizing of the alleged self-relgulation of the market's mechanisms advocated by the neoliberal utopian thought. In the third chapter, we analyse in which way Assmann incorporates the theory of living self-regulative systems to his thought about the market and begins to accept that, in some parts, the market is a self -regulating system and has a positive dimension. Here Assmann criticizes the neoliberal's idolatrous faith in a self-regulation that will always produce the best result. This impedes any attempt of a social intervention as a consequence of solidarity purposes which would compensate the exacerbated system's exclusion logic. In this interim, we will try to present a socioeconomic basis for the fact that it is impossible to put an end to the market and to the mercantile relations in wide and complex realities such as those from modern societies. Finally, we will also investigate how Assmann introduces the conception of solidarity in this discussion, both to criticize the idolatry of the market's complete automatism and to propose an estrategy to overcome this logic of sacrifice that ignores the tendency of exclusion in the market. To this end, we will make use mainly of DEI theologians' contributions as reference for analysing the work of Assmann and other philosophers and sociologists that are important from our point of view.